Comparing Outcomes of Two Types of Bariatric Surgery in an Adolescent Obese Population: Roux-en-Y Gastric Bypass vs. Sleeve Gastrectomy - Maffazioli, Giovana D.; Stanford, Fatima Cody; Campoverde Reyes, Karen J.; Stanley, Takara L.; Singhal, Vibha; Corey, Kathleen E.; Pratt, Janey S.; Bredella, Miriam A.; Misra, Madhusmita (Frontiers in Pediatrics, 2016)
Background Obesity is prevalent among adolescents and is associated with serious health consequences. Roux-en-Y Gastric Bypass (RYGB) and Sleeve Gastrectomy (SG) are bariatric procedures that cause significant weight loss in adults and are increasingly being performed in adolescents with morbid obesity. Data comparing outcomes of RYGB vs. SG in this age-group are scarce. This study aims to compare short-term (1–6 months) and longer-term (7–18 months) body mass index (BMI) and biochemical outcomes following RYGB and SG in adolescents/young adults. Methods A retrospective study using data extracted from medical records of patients 16–21 years who underwent RYGB or SG between 2012 and 2014 at a tertiary care academic medical center. Results Forty-six patients were included in this study: 24 underwent RYGB and 22 underwent SG. Groups did not differ for baseline age, sex, race, or BMI. BMI reductions were significant at 1–6 months and 7–18 months within groups (p < 0.0001), but did not differ by surgery type (p = 0.65 and 0.09, for 1–6 months and 7–18 months, respectively). Over 7–18 months, within-group improvement in low-density lipoprotein (LDL) (−24 ± 6 in RYGB, p = 0.003, vs. −7 ± 9 mg/dl in SG, p = 0.50) and non-high-density lipoprotein (non-HDL) cholesterol (−23 ± 8 in RYGB, p = 0.02, vs. −12 ± 7 in SG, p = 0.18) appeared to be of greater magnitude following RYGB. However, differences between groups did not reach statistical significance. When divided by non-alcoholic steatohepatitis stages (NASH), patients with Stage II–III NASH had greater reductions in alanine aminotransferase levels vs. those with Stage 0–I NASH (−45 ± 18 vs. −9 ± 3, p = 0.01) after 7–18 months. RYGB and SG groups did not differ for the magnitude of post-surgical changes in liver enzymes. Conclusion RYGB and SG did not differ for the magnitude of BMI reduction across groups, though changes trended higher following RYGB. Further prospective studies are needed to confirm these findings.